Supramolecular and Materials Applications of Tetrazines - Black, Martin (2025)
Tetrazines are a functional group with emerging applications in materials. The ability to undergo the inverse electron-demand Diels-Alder (IEDDA) reaction with alkenes and alkynes has emerged as a leading click reaction. This makes tetrazine a perfect choice for post-assembly modification (PAM) on metal organic cages (MOCs), and rotaxanes. In order to form new supramolecular structures such as MOCs it is often needed to repeat the process of ligand design and synthesis however with the tetrazine moiety as part of the backbone the structures can be modified with an array of alkenes/alkynes allowing tailored modification of the molecules. Throughout this thesis tetrazines were synthesised with PAM in mind. Chapter two highlights the methodologies used, specifically NMR spectroscopy, mass spectrometry, SCXRD, and CV with a specific focus on the investigation of supramolecular structures as a combination is needed to confirm product formation. Chapter three investigates the assembly of tetrazine edged MOCs using Pd(II) metal nodes to form a tetrahedral Pd4L8 assembly. The IEDDA reaction of the cage with an array of alkenes including norbornadiene, norbornene derivatives and cyclopentene was investigated with a focus on the structural transformations to Pd2L4 lanterns that take place by the introduction of flexibility in the rigid ligand. The process of assembly and PAM was followed by NMR spectroscopy, ESI-MS and SCXRD. The PAM led to a reduction in the angle between ligand vectors from an average of 63.1° to 7.2°. Single crystals of dihydropyridazine intermediates showed preferential formation of a sole isomer with maximum hydrogen bonding and high symmetry which was investigated. To the best of my knowledge the PAM with alkenes other than norbornadiene, had not been studied in the literature. The sequential oxidation of the dihydropyridazine intermediates via chemical oxidant was attempted and showed secondary structural changes to Pd4L8 and Pd3L6 topologies, as ligand planarity returned. This demonstrated that simple ligand alterations have distinct consequences on structure. The assembly of similar Pt(II) MOCs was also attempted and compared with the Pd(II) analogue. Chapter four focuses on the formation of tetrazine-based rotaxanes using dimethoxypillar[5]arene as a macrocycle. Rotaxanes with tetrazines as components of the axle are sparse in the literature. Much work has been done on controlling the reactivity of tetrazines towards the IEDDA through chemical effects however the rotaxane provides the opportunity to affect the reactivity through a mechanical bond. Therefore a variety of tetrazine incorporating axles were synthesised, both with aryl and alkyl substituents. Tetrazines substituted with pyridines at the 3 and 6 positions showed poor stoppering, and limited association with both pillar[5] and pillar[6]arene macrocyles. Tetrazines with alkyl imidazole substituents showed improved association with dimethoxypillar[5]arene macrocycle, mass spectrometry suggested the formation of [2] and [3]rotaxanes. The formation of rotaxanes was alkyl chain dependent with the pillar[5]arene requiring an alkyl chain more than two carbons long to induce association.The focus in Chapter five shifts to investigate the role substituted tetrazines play as redox mediators in lithium sulfur batteries. Lithium battery technology is looking beyond lithium-ion batteries as the theoretical potential is reached. Tetrazine can be reversibly reduced to the radical anion which made it a potential candidate as a redox shuttle in Li-sulfur batteries, an emerging next generation batteries technology. A library of tetrazines were screened with reduction potentials in the correct position to help reduce the polysulfide, acting as redox shuttles. A couple of the tetrazines appeared to be acting as a redox catalyst shown via cyclic voltammetry and showed improved performance during cell cycling. Steps to understand the mechanism were taken however this currently continues to remain unknown.